Effect of Maternal Body Mass Index and Amniotic Fluid Index on the Accuracy of Sonographic Estimation of Fetal Weight in Late Gestation - Blitz, Matthew J.; Rochelson, Burton; Stork, Leah B.; Augustine, Stephanie; Greenberg, Meir; Sison, Cristina P.; Vohra, Nidhi (American Journal of Perinatology, 2018)
Objective The objective of this study was to determine the effect, if any, of maternal body mass index (BMI) and amniotic fluid index (AFI) on the accuracy of sonographic estimated fetal weight (EFW) at 40 to 42 weeks' gestation.Methods This was a retrospective cohort study of singleton gestations with ultrasound performed at 40 to 42 weeks from 2010 to 2013. In this study, patients with documented BMI and sonographic EFW and AFI, concurrently, within 7 days of delivery were included. Chronic medical conditions and fetal anomalies were excluded from this study. The primary variable of interest was the rate of substantial error in EFW, defined as absolute percentage error (APE) >10%.Results A total of 1,000 pregnancies were included. Overall, the APE was 6.0 ± 4.5% and the rate of substantial error was 17.4% (n = 174). There was no significant difference in APE or rate of substantial error between BMI groups. In the final multivariable logistic regression model, the rate of substantial error was increased in women with oligohydramnios (OR 1.79; 95% CI: 1.10–2.92). Furthermore, oligohydramnios was significantly more likely to overestimate EFW while polyhydramnios was more likely to underestimate EFW. Maternal BMI did not affect the accuracy of sonographic EFW.Conclusion Sonographic EFW may be affected by extremes of AFI in the postdates period. Maternal BMI does not affect EFW accuracy at 40 to 42 weeks.
Keywords: estimated fetal weight; amniotic fluid index; oligohydramnios; polyhydramnios; obesity; body mass index